Technological and Methodological Approaches to the Design of Information and Educational Space of Modern High School - Eliseeva, Elena; Shcherba, Irina; Morozova, Svetlan; Shadoba, Elena; Petukhova, Larisa; Seregina, Natalia (International Review of Management and Marketing, 2016)
The paper discusses the technological and methodological approaches to the design of information and educational space of the modern university in the widespread use of new information and communication technologies to significantly improve the quality of training, learning to make personalized, intense, advancing and developing. The authors have given detailed interpretation of the concept of “information and educational space” considered its main elements and functions. It revealed the most important advantages offered by the modern university properly formed educational space. Reflect technological and methodological foundations of design information and educational space of the university, as well as the implementation phases of the project. Particular attention is paid to the means of information and educational space, which provide its constituencies to perform a number of important functions, including the development of innovative solutions for the automation and informatization of educational process. It is shown that an important component of design information and educational space of the university is the development and standardization of information resources. The submissions have applied value for specialists in the field of design information and educational environments and spaces, as well as teachers seeking to integrate successfully into the modern system of vocational training. Keywords: informational and educational space, infrastructure, education JEL Classifications: H75; I2